OBTAINING DERIVATIVES OF HUMIC SUBSTANCES FROM OXIDIZED COAL AND STUDY OF PHYSICO-CHEMICAL AND ADSORPTION PROPERTIES - Yermagambet Bolat Toleukhanuly; Kazankapova Maira Kuttybaevna; Kassenova Zhanar Muratbekovna; Nauryzbaeva Asemay Turlangyzy (Academic Scientific Journal of Chemistry, 2020)
In the work, a chemical analysis of humic substances based on oxidized coal of the Maikuben basin (Kazakhstan) is carried out. Humic acids were obtained on the basis of potassium humates by acidification with a 20% acid solution to pH = 3-4.5. The optimal conditions for obtaining nitrohumic acids from oxidized coals are: the duration of the process is 3 hours, the ratio of S:L = 1:5, the content of nitric acid is 64%, sulfuric acid is 96% and the composition of the nitrating mixture is 1:1 (g/g). Amminohumic derivatives were obtained in the presence of a 3% aqueous solution of ammonia using mechanical activation and ultrasonic treatment. The samples obtained were tested as an adsorbent for water purification from heavy metals. Humic acids and aminohumate showed the highest degrees of purification for zinc (99.0-100.0%) and cadmium (80.0-96.7%), and nitrohumic acid showed a high adsorption capacity for heavy metals like copper - 100.0 % and lead 82.9%. This is due to the fact that when interacting with heavy metals, humic acids and their derivatives (amino and nitro) form chelate complexes due to carboxyl, phenolic, nitro and amino groups. As a result of the study, the possibility of using them as non-toxic available sorbents for the purification of heavy metals in aqueous media has been shown.